A growth model to predict body weight and body composition of broilers - Dukhta, Galyna; van Milgen, Jaap; Kövér, György; Halas, Veronika (Acta Agraria Debreceniensis, 2018)
Models predicting the nutrient partitioning and animal performance have been developed for decades. Nowadays, growth models are used in practical animal nutrition, and they have particular importance in precision livestock farming. The aim of the present study was to introduce a broiler model and to provide examples on model application. The model predicts protein and fat deposition as well as the body weight of an individual broiler chicken from digestible nutrient intake over time. Feed intake (FI) and the digestible nutrient content of the feed are inputs as well as some animal factors like: initial BW, feed intake at 1 and 2 kg of BW, precocity and mean protein deposition. The protein and energy metabolism is represented as in the classical nutrient partitioning models. The protein deposition (PD) is driven by digestible amino acid supply and is under “genetic control”, the so-called potential PD limits the actual PD if protein is oversupplied.The authors discuss how the model can be used to simulate the animal response upon different scenarios. Examples are given to show that the diet might be limiting if some animal trait is changed. Applicability of the model has shown through running the model by using different feed strategies (three- vs five-phase-feeding) and variations with animal factors. In conclusion, growth models are useful tools to support decision making for defining the most suitable feeds used in a broiler farm. The model presented in this paper shows a high sensibility and flexibility to test different scenarios. By challenging the model with different inputs, the animal response in terms of changes in body weight and feed conversion can be understood more by studying the shift in deposition of chemical constituents. The examples provided in the present paper shows the benefit of using mathematical models and their applicability in precision nutrition. It can be concluded that the growth model helps to apply “from desired feed to desired food” concept.